THE ANTECEDENTS OF CUSTOMER RELATIONSHIP MANAGEMENT PERFORMANCE AN EMPIRICAL INVESTIGATION IN JORDAN MOBILE PHONE SERVICES - Wahab, Samsudin; Al-Momani, Khalid; Mohd Noor, Nor Azila (International Business Education Journal, 2009)
Customer relationship management performance (CRM) is to establish the relationship between customer and service providers. Therefore, the tangible and intangible results of e-customer relationship management performance are repeat purchase, word of mouth, retention, brand loyalty and customer satisfaction. The increasing numbers of mobile phone users all over the world has influence the researchers to investigate the antecedent of Customer relationship management performance in this service country. 850 questionnaires have returned, however, 488 were analysed due to incomplete and missing data problem. Five technology factors been tested as the main antecedent for customers relationship management performance; trust, commitment, privacy and usefulness. Electronic service quality has failed to predict e-customer relationship management performance. As a contribution this paper ends with discussion, conclusion and suggestion for the managers in improving their customer relationship management performance especially in mobile phone industry.